Properties Of Particleboards Made From Oil Palm Trunk With Addition Of Poly-3-Hydroxybutyrate - Baskaran, Mohana (2011)

(untitled)
This study was designed to evaluate the influence of adding poly-3-hydroxybutyrate [P(3HB)] on the properties of particleboards made from oil palm (Elaeis guinensis) trunk. Two types of boards which are particleboards made up of steam treated particles and untreated particleboards, were manufactured from oil palm trunk particles with a target board density of 0.8 g/cm3, pressing temperature of 180 °C, pressing pressure of 5 MPa and pressing time of 20 min. The steam treatment was carried out by subjecting the oil palm trunk particles at a temperature of 130 °C for 30 min before those particles was used for particleboard production.